Rethinking Muslim Family Education in the Society 5.0 Era: An Islamic Educational Framework in Global Perspective - Syahfrudin, Arif; Ningsih, Tutuk; Yahya, Slamet (Journal of Islamic Education Research, 2026)
This study aims to reconceptualize Muslim family education in the Society 5.0 era by examining the interaction between Islamic educational values, digital transformation, and contemporary global educational discourse. The study addresses a critical gap in the literature, as existing research on digital parenting often emphasizes technical or behavioral control while giving limited attention to the integration of moral, spiritual, and character dimensions that are central to Islamic education. Therefore, this research seeks to develop an integrative framework that aligns spiritual formation, character education, and digital competence within the family context. Methodologically, this study employs a qualitative Systematic Literature Review. Peer reviewed publications on Muslim family education, character development, and digital parenting published between 2020 and 2026 were systematically selected and analyzed using thematic analysis to identify conceptual trends, theoretical gaps, and recurring patterns. The findings reveal a significant structural and pedagogical transformation in Muslim families, shifting from traditional caregiving roles toward multidimensional educational functions as primary educators, value based digital companions, and moral role models. Islamic values remain the ethical foundation of parenting but are increasingly enacted through dialogical communication, reflective mediation of technology use, and collaboration with schools and communities. Three interrelated dimensions of effective family education are identified, namely spiritual intelligence, emotional intelligence, and digital intelligence, which collectively foster morally grounded, emotionally mature, and digitally responsible children. This study contributes theoretically by extending Islamic family education discourse into the Society 5.0 paradigm, conceptually by proposing a holistic integrative model of family based character education, methodologically by synthesizing fragmented interdisciplinary research through a systematic review, and practically by providing strategic guidance for parents, educators, and policymakers in strengthening value oriented digital parenting in technologically mediated societies.